The dopamine receptor agonist apomorphine stabilizes neurotoxic α‐synuclein oligomers. Issue 3 (29th December 2021) - Lima, Vanderlei de Araujo; Esquinelato, Rodrigo; Carmo‐Gonçalves, Phelippe; Nascimento, Lucas Alex do; Lee, Hudson; Eliezer, David; Romão, Luciana; Follmer, Cristian
Abstract : The misfolding and aggregation of the protein α‐synuclein (aSyn) into potentially neurotoxic oligomers is believed to play a pivotal role in the neuropathogenesis of Parkinson's disease (PD). Herein, we explore how apomorphine (Apo), a nonselective dopamine D1 and D2 receptor agonist utilized in the therapy for PD, affects the aggregation and toxicity of aSyn in vitro . Our data indicated that Apo inhibits aSyn fibrillation leading to the formation of large oligomeric species (Apo‐aSyn‐O), which exhibit remarkable toxicity in mesencephalic dopaminergic neurons in primary cultures. Interestingly, purified Apo‐aSyn‐O, even at very low concentrations, seems to be capable of converting unmodified aSyn monomer into neurotoxic species. Collectively, our findings warn for a possible dangerous effect of Apo on aSyn misfolding/aggregation pathway. Abstract : This study demonstrates that apomorphine (Apo) inhibits the in vitro fibrillation of the Parkinson's disease‐linked protein α‐synuclein (aSyn) and promotes the stabilization of large oligomers of the protein with remarkable toxicity in mesencephalic neurons in culture. These findings point to the necessity of further studies on the influence of catechol antiparkinsonian drugs on the toxicity mediated by aSyn aggregation.